Maternal hemoglobin concentration and hematocrit values may affect fetus development by influencing placental angiogenesis. (17th January 2017) - Stangret, Aleksandra; Wnuk, Anna; Szewczyk, Grzegorz; Pyzlak, Michał; Szukiewicz, Dariusz
Abstract: Objective : Vasculogenesis and angiogenesis are crucial for maintaining proper placental perfusion and optimal fetal development. Among other physical and chemical factors, hypoxia is known to stimulate angiogenic processes. Preplacental type of hypoxia is often associated with maternal anemia and is thought to enhance vascularization within the fetoplacental unit. The goal of this study was to establish the correlation between the local expression of vascular endothelial growth factor (VEGF) and placenta growth factor (PlGF) receptors (flt-1, flk-1) with maternal hemoglobin (Hb) concentration, hematocrit (Ht) values and the infant birthweight. Methods : In total, 43 specimens of term placentas obtained from normal course pregnancies delivered at term were included in the study. The expression of flt-1 and flk-1 receptors was analyzed by immunohistochemical staining. Vascular/extravascular tissular index (V/EVTI) was measured by assessing a total vascular area. Nonparametric Mann–Whitney U-test and Spearman's rank correlation were used to compare the various parameters and their differences between the groups. Results : Among the patients with low Hb concentration, nearly 2-fold greater expression of the flt-1 receptor was positively correlated with infants birthweight ( p = 0.028). Conclusions : Increased placental vascular density (increased flt-1 expression), during a physiological course of gestation, may be an adaptive response to lowered maternal Hb concentration and Ht values encountered during pregnancy.